2017
DOI: 10.1155/2017/2813816
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Investment Timing and Size of a Logistics Park: A Real Options Perspective

Abstract: This paper uses a real options approach to address optimal timing and size of a logistics park investment with logistics demand volatility. Two important problems are examined: when should an investment be introduced, and what size should it be? A real option model is proposed to explicitly incorporate the effect of government subsidies on logistics park investment. Logistic demand that triggers the threshold for investment in a logistics park project is explored analytically. Comparative static analyses of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Spatial siting, functional area arrangement, distribution route planning, park scale and investment timing are the important factors affecting the high-quality development of logistics parks and they have become the focus of scholars' attention. For example, Xu [17] proposed a heuristic algorithm-based logistics park site selection model, Luo [18] created a two-stage layout method for the functional area of the logistics parks, Liang [19] proposed an optimization approach for the distribution path of the logistics park based on the improved artificial bee colony algorithm, and Zhang [20] analyzed the optimal investment time and scale of the construction of the logistics park from the perspective of real options.…”
Section: Logistics Land and Logistics Parkmentioning
confidence: 99%
“…Spatial siting, functional area arrangement, distribution route planning, park scale and investment timing are the important factors affecting the high-quality development of logistics parks and they have become the focus of scholars' attention. For example, Xu [17] proposed a heuristic algorithm-based logistics park site selection model, Luo [18] created a two-stage layout method for the functional area of the logistics parks, Liang [19] proposed an optimization approach for the distribution path of the logistics park based on the improved artificial bee colony algorithm, and Zhang [20] analyzed the optimal investment time and scale of the construction of the logistics park from the perspective of real options.…”
Section: Logistics Land and Logistics Parkmentioning
confidence: 99%
“…A logistics park is an important logistics facility that can significantly impact not only economic efficiency in the movement of goods and commodities (as discussed above) but also the environment. It can, for instance, reduce carbon dioxide emissions and air pollution by combining multiple distribution centers and logistic operators into a single park (Zhang et al 2017). There is a growing trend to introduce logistics parks in both the developed and developing countries.…”
Section: Improve the Attractiveness Of Special Economic Zones And Ind...mentioning
confidence: 99%
“…It is suggested that the trade and investment facilitation cluster work together with relevant government authorities to promote the setting up of logistics zones equipped with storage and transport services, public facilities (for industry and commerce, taxation, customs, commodity inspection, banking, insurance, and other service facilities); and related facilities (with the office, accommodation, catering, and other services facilities). A logistics park can have a significant impact not only on economic efficiency in the movement of goods and commodities but also on the environment by reducing, for instance, carbon dioxide emissions, and air pollution through combining multiple distribution centers and logistic operators into a single park (Zhang et al 2017).…”
Section: Strategic Intervention 2: Address High Logistics Costs By En...mentioning
confidence: 99%